(untitled) - Edwin H McConkey (Boston, 1993)
This is survey of human genetics for students and professionals in biology and medicine. It focuses on fundamental knowledge about genome organization, function, and variation, as well as the understanding, diagnosis, and treatment of genetic disease. Throughout the book, there is an emphasis on understanding human genetics in molecular terms
Keywords: medical genetics